2005
DOI: 10.2169/internalmedicine.44.124
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss Combined with Takayasu's Arteritis

Abstract: A 49-year-old woman complained of hearing loss and diminution of left radial arterial pulsation. She had been diagnosed with sudden deafness and treated with corticosteroids. Her audibility deteriorated again after the cessation of the therapy. Angiograms showed stenosis in the bilateral carotid arteries, the left vertebral artery, the left subclavian artery, and the pulmonary arteries. She was diagnosed with Takayasu's arteritis. After steroid therapy was restarted, there were improvements in her audibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…IL-6 levels are higher than normal in the serum of patients with Takayasu arteritis during the active phase, and their serum concentrations are positively correlated with disease activity, including sensorineural hearing loss [8] . Similarly, IL-6 levels are decreased in proportion to the reduction of disease activity and hearing loss.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…IL-6 levels are higher than normal in the serum of patients with Takayasu arteritis during the active phase, and their serum concentrations are positively correlated with disease activity, including sensorineural hearing loss [8] . Similarly, IL-6 levels are decreased in proportion to the reduction of disease activity and hearing loss.…”
Section: Discussionmentioning
confidence: 95%
“…The effects of proinflammatory cytokines on cochlear function have been investigated in recent studies [5][6][7][8][9] . Cytokines are supposed to contribute to the development of hearing loss by their effects, consistent with systemic inflammation and tissue damage through fluid hemostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensorineural hearing loss (SNHL) is a well-recognized manifestation of various systemic vasculitides, such as antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides [3,4] and Cogan's syndrome [2]; however, in patients with TAK, only a few cases of SNHL have been reported in the English literature. Accordingly, the pathogenesis remains poorly understood, and there is no established treatment strategy for SNHL [5][6][7][8][9][10][11]. We herein report the clinical findings in a patient with TAK who developed sudden bilateral deafness and underwent bilateral cochlear implants.…”
Section: Introductionmentioning
confidence: 90%
“…HL mainly presents as sudden sensorineural hearing loss (SSNHL) and responds to corticosteroid therapy [2] . In the authors' opinion, the reasons for misdiagnosing HL in patients with TA are lack of evidence regarding this rare complication and because TA involves large caliber arteries, instead of small vessels that are typical of the inner ear.The etiology of HL in TA remains unknown [3] ; it has been speculated that HL follows the elevation of serum immune complexes that deposits in the inner ear or reversible circulatory disturbances with hypercoagulability in response to the arterial disease [2] . Noel et al [4] reported that the occlusion of small retinal vessels is a rare and severe microcirculatory complication in TA; common immunopathology mechanisms with HL could be hypothesized.…”
mentioning
confidence: 99%